Linguagem narrativa e fluência na síndrome de down: uma revisão - Seno, Marília Piazzi; Giacheti, Célia Maria [UNESP]; Moretti-ferreira, Danilo (CEFAC Saúde e Educação, 2014)
Down’s syndrome is a condition in which individuals have intellectual impairment and oral language disorders. Speech disfluency is present during both spontaneous conversations as in productions of directed oral narratives. This study aimed to review the published literature between 2002 and 2012 in eletronic databases on disfluency and narrative in individuals with Down syndrome. There were 17 articles and eight were selected according to the criteria of inclusion and exclusion. Two of these articles specifically discoursed on dysfluency in Down’s syndrome and the other six on the narrative in this population. Intellectual disability is part of the phenotype of individuals with DS and, as a result of the intellectual impairment, losses occur on the acquisition and development of language. Specific studies about, mainly on fluency/disfluency, and the performance on a task of narrative and, are still scarce and inconclusive. Disfluency doesn’t appear in most descriptions of the language phenotype of individuals with this condition, which would deserve additional clinical studies.

A síndrome de Down é uma condição na qual os indivíduos apresentam comprometimento intelectual e alterações de linguagem oral. A disfluência de fala está presente tanto durante a conversa espontânea como em produções orais de narrativas direcionadas. Este estudo teve como principal objetivo revisar a literatura sobre a disfluência e a narrativa em indivíduos com a síndrome de Down, publicada entre 2002 e 2012, em bases de dados eletrônicos. Foram encontrados 17 artigos e selecionados oito, de acordo com os critérios de inclusão e exclusão. Destes, dois discorriam especificamente sobre a disfluência na síndrome de Down, e seis sobre a narrativa nesta população. A deficiência intelectual é parte do fenótipo dos indivíduos com SD e, em decorrência do comprometimento intelectual, prejuízos na aquisição e no desenvolvimento da linguagem. Estudos específicos, principalmente sobre a fluência/disfluência; e, sobre o desempenho na tarefa da narrativa, ainda são escassos e inconclusivos. A disfluência não aparece na maioria das descrições do fenótipo de linguagem dos indivíduos com esta condição, que mereceria, estudos clínicos adicionais.
Narrative language and fluency in down syndrome: a review
Keywords: Síndrome de Down; Narração; Gagueira; Down Syndrome; Narration; Sttutering